Starch fatty esters for potential use in petroleum industry - Dias, Fernanda; de Souza, Roberta; Lucas, Elizabete (Publishing House of Lviv Polytechnic National University, 2013)
The aim of this study was to obtain and characterize starch fatty esters with variations in the hydrophilic/lipophilic balance and to assess whether these samples have potential application in oil-based drilling fluids. The variation in the hydrophobicity of the samples was verified by means of viscosity tests, which suggested that the products had varied solubility parameters, near the value of the solvent n-paraffin. Отримано і охарактеризовано жирні естери крохмалю при зміні гідрофільно/ліпофільного балансу. Проведено оцінку можливості їх потенційного застосування в бурових розчинах на нафтовій основі. Зміна гідрофобності зразків підтверджена випробуваннями в‘язкості, які довели, що продукти мають різні параметри розчинності, поблизу значення розчинника н-парафіну.
Естери жирних кислот та крохмалю для потенційного використання у нафтовій промисловості
Keywords: modified starch; fatty acid esters; transesterification; n-paraffin; drill fluid; модифікований крохмаль; естери жирних кислот; переестерифікація; н-парафін; буровий розчин